2022
DOI: 10.1007/s00018-022-04599-2
|View full text |Cite
|
Sign up to set email alerts
|

GLI1+ cells are a source of repair-supportive mesenchymal cells (RSMCs) during airway epithelial regeneration

Abstract: Repair-supportive mesenchymal cells (RSMCs) have been recently reported in the context of naphthalene (NA)-induced airway injury and regeneration. These cells transiently express smooth muscle actin (Acta2) and are enriched with platelet-derived growth factor receptor alpha (Pdgfra) and fibroblast growth factor 10 (Fgf10) expression. Genetic deletion of Ctnnb1 (gene coding for beta catenin) or Fgf10 in these cells using the Acta2-Cre-ERT2 driver line after injury (defined as NA-Tam condition; Tam refers to tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…Bulk RNA-seq data were deposited on Gene Expression Omnibus, accession number GSE253415. The accession number for the single-cell RNA-seq dataset from the hypoxia condition is GSE260788, while that for normoxia is GSE215094 (uninjured lung in the study by Chu et al 22 ).…”
Section: Methods Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk RNA-seq data were deposited on Gene Expression Omnibus, accession number GSE253415. The accession number for the single-cell RNA-seq dataset from the hypoxia condition is GSE260788, while that for normoxia is GSE215094 (uninjured lung in the study by Chu et al 22 ).…”
Section: Methods Data Availabilitymentioning
confidence: 99%
“…21 We have also recently shown that GLI1+ cells contribute to airway regeneration and subepithelial remodeling. 22 In this study, we hypothesized that perivascular GLI1+ cells contribute to newly formed ACTA2+ cells in the pulmonary vasculature of mice exposed to hypoxia or cigarette smoke. We used genetic lineage tracing combined with state-of-the-art imaging and flow cytometry to quantify and analyze lineage-labeled and ACTA2+ cells during VR and reverse remodeling (RR).…”
Section: Novelty and Significancementioning
confidence: 99%
“…Recent studies have shown that L-MSCs may constitute a rather heterogenous population and their study might require more advanced methods, such as scRNA-seq or sc-proteomics [ 292 , 293 ]. Another recently emerging candidate resident MSC population are the Gli-1 + repair-supportive mesenchymal cells [ 298 , 299 ]. Progenitor properties of Gli-1 + cells were previously described in other organs, including bones [ 300 , 301 ], teeth [ 300 ], and liver [ 302 ].…”
Section: Novel Approaches To Study the Preterm Lungmentioning
confidence: 99%
“…Progenitor properties of Gli-1 + cells were previously described in other organs, including bones [ 300 , 301 ], teeth [ 300 ], and liver [ 302 ]. In the lung, Gli-1 + cells co-express Acta2 , Fgf10 and Pdgfra , thus resembling alveolar fibroblasts [ 225 , 298 ]. In mice Gli-1 + MSCs were shown to aid epithelial regeneration following naphthalene-induced airway injury [ 298 ], and were shown to be increased in bleomycin-induced lung fibrosis in mice [ 303 ].…”
Section: Novel Approaches To Study the Preterm Lungmentioning
confidence: 99%
See 1 more Smart Citation